Comparison of phenotypic variability of winter durum wheat varieties and lines according to the color characteristics of grain, cereals and pasta - N. S. Kravchenko; O. A. Kostylenko; N. G. Ignatieva; A. S. Ivanisova (Зерновое хозяйство России, 2024)
There have been given the study results of grain color characteristics of winter durum wheat varieties and lines (Triticum durum Desf.). There has been studied the effect of factors (‘variety’, ‘year’ and their correlation) on the expression of the main breeding-valuable traits that affect the quality of the final product. The purpose of the current study was to determine the variability of phenotypic characteristics of grain associated with the number of yellow pigments in grain, the color of semolina and finished pasta, to study the correlation between indicators and to identify the most promising ones for further work. Field trials were carried out in the scientific crop rotation laboratory of breeding and seed production of winter durum wheat of the FSBSI “ARC “Donskoy”. Laboratory and analytical study was carried out in the laboratory of biochemical, technological and agrochemical estimation in accordance with generally accepted methods and GOST. As a result of the study, there has been established that the main effect on such characteristics of grain quality of winter durum wheat as ‘general hardiness’, ‘mass fraction of protein in grain’ and ‘grain color index b’ was produced by the factor ‘year of study’ by 67.0 %, 48 .2 % and 65.4 % respectively. The ‘cereal color index b’, ‘dry pasta color index b’ and visual estimation of dry pasta were mainly influenced by the factor ‘genotype’ by 62.3 %, 82.5 % and 48.3 %, respectively. The severity of the trait ‘content of carotenoid pigments’ depended on all factors. Over the years of the study, the winter durum wheat varieties and lines developed by the FSBSI “ARC “Donskoy” according to color characteristics met the international requirements for durum wheat grain. As a result, the varieties ‘Grafit’ and ‘Karotinka’ stood out according to several studied characteristics in connection with which we recommend expanding the production crops of these varieties. There can be recommended to use promising lines 1147/19 and 971/19 and the variety ‘Solntsedar’ in the breeding process as sources with high color characteristics of grain and pasta.